Pengaruh Motivasi Kerja terhadap Kinerja Karyawan pada PT Subur Plus (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of work motivation on employee performance at PT Subur Plus. Work motivation is considered one of the crucial factors in enhancing both individual and team performance. The research employs a quantitative approach using a survey method with questionnaires distributed to 50 permanent employees in the operational and administrative divisions. Work motivation is measured through intrinsic and extrinsic factors, while employee performance is assessed based on quantity, quality, timeliness, and responsibility. The results of the analysis indicate that work motivation has a positive and significant effect on employee performance. The coefficient of determination (R²) of 94.7% shows that most of the variation in employee performance is influenced by work motivation. These findings highlight the importance of implementing effective strategies to enhance employee motivation through training programs, rewards, and the development of a supportive work environment.